Pemilihan Umum dan Pemilihan Presiden dan Wakil Presiden Secara Langsung Perspektif Keumatan (Agama) - Amir Mu'allim (Unisia, 2004)
If we look back to the era of the Prophet Muhammad PBUH and the Era of Companions, we can find other prespective to see political system which we can compare to the democratic system. In the Islamic context (imamah) there's no specific model to follow, but Islam give more chance and open more space to moslems how to choose their leader. But, the most important point is that Muslim must consider the concept of shura, whereas shura/musyawarah is been recognized as a core value of democracy.